A non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier, preparation method and application

By doping phosphorus elements into the lanthanum iron-based perovskite oxygen carrier, LaFe1-xPxO3 oxygen carrier was prepared, which solved the problems of low reactivity of the oxygen carrier and high tar content, and achieved the effect of improving the yield of biomass gasification synthesis gas and reducing tar content.

CN117185274BActive Publication Date: 2025-03-07NANJING TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311203381.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-03-07
Estimated Expiration
2043-09-19

AI Technical Summary

Technical Problem

In the existing biomass chemical chain gasification reaction, the oxygen carrier reacts with low reaction activity, low yield of biomass gasification synthesis gas and high tar content, the acid and alkalinity of the perovskite oxygen carrier surface is difficult to mix and the reaction activity is poor.

Method used

A non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier is used, with the general formula LaFe1-xPxO3, 0≤x≤1. By ammonium dihydrogen phosphate as the phosphorus dopant, an oxygen carrier with good structural stability and improved acidity and reactive activity on the surface of the oxygen carrier is prepared.

Benefits of technology

Effectively improve the acidity of the oxygen carrier surface, modulate its surface reactive activity and lattice oxygen migration ability, improve the carbon conversion rate and synthesis gas yield of biomass, and reduce the tar content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117185274B_ABST
    Figure CN117185274B_ABST
Patent Text Reader

Abstract

The present invention discloses a non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier, a preparation method and an application thereof. The general formula of the oxygen carrier is LaFe 1‑x P x O3. In the biomass gasification stage, the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier exchanges heat and mass with the biomass, and the lattice oxygen in the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier partially oxidizes the biomass to generate synthesis gas, while the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier is reduced to generate a reduced oxygen carrier; in the oxidation stage, the reduced oxygen carrier reacts with oxygen in the air to achieve oxygen replenishment and restores to the structure before the reaction with the biomass, thereby achieving the cyclic regeneration of the oxygen carrier. The oxygen carrier can effectively improve the surface acidity of the oxygen carrier, and adjust its surface reactivity and lattice oxygen migration ability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of oxygen carriers, and in particular, relates to a non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier, a preparation method and an application thereof. Background Art

[0002] The continued reliance of the world's economic development on fossil energy has led to an increase in greenhouse gas emissions, mainly CO2, year by year. The resulting global climate change has become one of the biggest challenges facing mankind in this century. Therefore, the development and utilization of renewable energy and the development of efficient and economical carbon emission reduction technologies have become a top priority to alleviate resource, energy and environmental problems. As the only carbon-neutral renewable energy, biomass has the advantages of recyclable resources, sustainable sources and storable energy. It is known as the world's "fourth largest energy source" after coal, oil and natural gas. The development and utilization of biomass energy can not only reduce the dependence of human social development on fossil energy, promote the transformation of the modern energy system, and promote the "green recovery" of the world economy after the epidemic, but also fix carbon and reduce emissions, helping to achieve the "dual carbon" goals.

[0003] Among the many biomass utilization technologies, the biomass gasification to produce syngas technology route has the advantages of energy efficiency, It has significant advantages in terms of efficiency and production cost, and is one of the ideal ways to effectively utilize biomass energy. Tar by-products are the biggest obstacle to the promotion and application of biomass gasification technology. The soot particles produced by tar combustion cause trouble for dust removal, and the liquid tar condensed at low temperatures can also cause pipeline blockage and pollution, affecting the gas utilization efficiency and the safe and stable operation of related equipment. The best way to deal with tar is to crack it into small molecular permanent gases, which can reduce the tar content while increasing the synthesis gas output. Therefore, studying the method of tar cracking is an urgent problem that needs to be solved. Although the use of oxygen as a gasification medium can effectively reduce the production of tar, the use of oxygen means that an air separation oxygen production device needs to be installed, which has high operating costs and complex system processes.

[0004] The biomass chemical looping gasification technology based on circulating oxygen carriers is a new type of biomass thermal conversion method with low system energy consumption, high calorific value of synthesis gas, low pollutant emissions, and high efficiency and cleanliness. It uses the lattice oxygen in the metal oxide (oxygen carrier) to replace part or all of the traditional gasification medium, and completes the transfer of lattice oxygen and heat and partial oxidation of biomass through the alternating circulation of oxygen carriers in the gasification reactor and oxidation reactor, while achieving self-heating operation. Compared with traditional biomass gasification technology, biomass chemical chain gasification has the following significant advantages: (1) The oxygen element required for biomass gasification is provided by the lattice oxygen in the metal oxide oxygen carrier, which avoids the energy consumption of using air separation equipment to prepare pure oxygen and preparing a large amount of water vapor, thereby reducing system costs; (2) The heat generated by the oxygen carrier during oxidation and regeneration in the oxidation reactor is brought into the gasification reactor to provide heat for biomass gasification. The oxygen carrier also acts as a heat carrier, without the need for an external heat source, thereby improving system efficiency; (3) Compared with gaseous oxygen, lattice oxygen is more conducive to partial oxidation of the fuel, thereby increasing the calorific value of the synthesis gas; (4) The oxygen carrier in the reducing atmosphere also acts as a catalyst, which can effectively catalyze the cracking of large molecular tar, thereby reducing the blockage and corrosion of tar on subsequent industrial equipment. The decomposition of tar is also conducive to increasing the yield of synthesis gas; (5) Since there is no introduction of other gases such as nitrogen, on the one hand, the quality of the synthesis gas is improved, and on the other hand, the generation of pollutants such as nitrogen oxides is effectively reduced at high temperatures.

[0005] In the chemical chain gasification process, the oxygen carrier is the hub connecting the two reactors. Therefore, screening oxygen carriers suitable for the chemical chain gasification process is crucial to improving the effect of the chemical chain gasification reaction. Although Fe-based oxygen carriers have obvious advantages in cost, their reactivity is poor and their oxygen carrying rate is low; Ni-based oxygen carriers have outstanding advantages in reactivity and catalytic tar cracking, but due to their low mechanical strength, high cost and harmful properties to the environment and human body, the development and application of Ni-based oxygen carriers are subject to certain restrictions; Cu-based and Mn-based oxygen carriers are often used in the chemical chain oxygen decoupling (CLOU) process due to their ability to release molecular oxygen, but molecular oxygen is more inclined to completely oxidize carbon-containing fuels than lattice oxygen. In addition, Cu-based oxygen carriers are easy to sinter under high temperature conditions, and Mn-based oxygen carriers have low mechanical strength and short particle life. Therefore, both have not been widely used in the chemical chain gasification process with syngas as the target product. As can be seen from the above, single metal oxygen carriers have their own advantages and are easy to obtain, but they also have their own disadvantages. In recent years, perovskite oxides have attracted much attention due to their unique ABO3 structural characteristics and have been found to have the potential to be oxygen carriers, among which LaFeO3 is the most widely used. Since the B-site element in this structure is an active phase, by doping the B-site element, the mobility of the oxygen in the lattice of the oxygen carrier can be increased, the generation of oxygen vacancies can be strengthened, and the surface acidity and alkalinity of the oxygen carrier can be improved, thereby achieving the structural regulation and performance reconstruction of the perovskite oxygen carrier, which provides an effective way to improve the quality of biomass chemical chain gasification syngas. However, the current research on the selection of elements for A and B-site doping of LaFeO3 is concentrated on metal elements. Although metal doping can effectively improve the performance of oxygen carriers, since metal doping generally uses the corresponding metal nitrate as a raw material, the cost is high and there are safety hazards such as explosion. In addition, the introduction of transition metal elements generally enhances the alkalinity of the active sites on the surface of the oxygen carrier, and the decomposition of organic macromolecules in biomass tar requires not only alkaline active centers, but also certain acidic sites to deprive H in the CH bond. - , so that the stable tar system is transformed into active positive carbon ions, creating favorable conditions for the breaking of CC bonds. Therefore, the existing technical problems in the existing biomass chemical chain gasification reaction are low reactivity of single metal oxides, low biomass gasification syngas yield and high tar content, and the acidity and alkalinity of the perovskite oxygen carrier surface are difficult to adjust and the reactivity is poor. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier, a preparation method and an application thereof, so as to effectively improve the surface acidity of the oxygen carrier and adjust its surface reaction activity and lattice oxygen migration ability.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] In a first aspect, an embodiment of the present invention provides a non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier, wherein the general formula of the oxygen carrier is LaFe 1-x P x O3, the value range of x is 0≤x≤1.

[0009] As a preferred example, the crystal structure of the oxygen carriers is cubic.

[0010] As a preferred example, the value range of x is 0.01≤x≤0.05.

[0011] In a second aspect, an embodiment of the present invention provides a method for preparing a non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier, the method comprising the following steps:

[0012] Step 10, according to LaFe 1-x P x O3 stoichiometric ratio, weigh 4.3300 parts by mass of La(NO3)3·6H2O, 4.0402(1-x) parts by mass of Fe(NO3)3·9H2O, 1.1503x parts by mass of NH4H2PO4, and a complexing agent, dissolve them in deionized water at a preset temperature, and add ammonia water dropwise to the solution to adjust the pH value of the solution to form a precursor solution;

[0013] Step 20, evaporating the precursor solution of step 10 to a gel state under stirring conditions, and then pre-combusting to obtain a sponge-like porous precursor;

[0014] Step 30, calcining the sponge-like porous precursor obtained in step 20 at a constant temperature to obtain the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier.

[0015] As a preferred example, in step 10, the complexing agent includes citric acid and ethylenediaminetetraacetic acid, the molar ratio of citric acid to ethylenediaminetetraacetic acid is 2:1, and the molar ratio of the complexing agent to the total amount of metal ions in the precursor solution is 3:1.

[0016] As a preferred example, in step 10, the preset temperature is 70-90° C., and the pH value of the precursor solution is 7-8.

[0017] As a preferred example, in the step 20, the stirring rate is 300-500 rpm, the evaporation temperature is 100-120°C, the pre-combustion is carried out in a muffle furnace, and the pre-combustion temperature is 250°C; in the step 30, the sponge-like porous precursor obtained in step 20 is transferred to a crucible and calcined at a constant temperature in the muffle furnace, the calcination temperature is 1000°C, and the calcination time is 5h.

[0018] In the third aspect, an embodiment of the present invention provides an application of a non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier in a biomass chemical chain gasification reaction. In the biomass gasification stage, the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier exchanges heat and mass with the biomass, and the lattice oxygen in the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier partially oxidizes the biomass to generate synthesis gas. At the same time, the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier is reduced to generate a reduced oxygen carrier; in the oxidation stage, the reduced oxygen carrier reacts with oxygen in the air to replenish oxygen and restores to the structure before the reaction with the biomass, thereby realizing the cyclic regeneration of the oxygen carrier.

[0019] As a preferred example, the raw material of the biomass is at least one of green algae, municipal sludge and cotton stalks, and the temperature of the gasification stage and the oxidation stage are both 750-950°C.

[0020] As a preferred example, in the biomass gasification stage, the gases introduced are nitrogen and water vapor, and the volume percentage of water vapor is 0-20%; in the oxidation stage, the gas introduced is air.

[0021] Compared with the prior art, the present invention has the following beneficial effects: the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier, preparation method and application of the present invention can effectively improve the surface acidity of the oxygen carrier, adjust its surface reactivity and lattice oxygen migration ability. The oxygen carrier is a perovskite structure, and its general formula is LaFe 1-x P x O3, 0≤x≤1. The use of the oxygen carrier in biomass chemical chain gasification reaction can improve the carbon conversion rate and synthesis gas yield of biomass. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 (a) is the XRD pattern of the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier prepared in Examples 1 to 4 of the present invention;

[0023] Figure 1 (b) Figure 1 The enlarged view of the dotted box in (a) is the enlarged spectrum of the diffraction peak with a diffraction angle between 31 and 33°;

[0024] FIG2( a) is a SEM image of the oxygen carrier LaFeO3 prepared in Example 1 of the present invention;

[0025] Figure 2(b) shows the oxygen carrier LaFe prepared in Example 3 of the present invention 0.97 P 0.03 SEM image of O3;

[0026] FIG2(c) is an EDX spectrum of the oxygen carrier LaFeO3 prepared in Example 1 of the present invention;

[0027] Figure 2(d) shows the oxygen carrier LaFe prepared in Example 3 of the present invention. 0.97 P 0.03 EDX spectrum of O3;

[0028] Figure 3 The thermogravimetric analysis results of biomass chemical chain gasification with various oxygen carriers at a heating rate of 40℃ / min;

[0029] Figure 4 (a) is a graph showing the mass spectrometry test results of hydrogen in the synthesis gas components during the thermogravimetric analysis of biomass chemical chaining gasification with various oxygen carriers;

[0030] Figure 4 (b) is a graph showing the mass spectrometry test results of carbon monoxide in the synthesis gas component during the thermogravimetric analysis of biomass chemical chaining gasification with various oxygen carriers;

[0031] Figure 5 The gas component distribution result diagram of direct gasification of municipal sludge and cotton stalk mixed biomass and quartz sand of comparative example 1 under the conditions of 850°C and 20% water vapor volume fraction;

[0032] Figure 6 The distribution result of gas components from chemical chain gasification of municipal sludge and cotton stalk mixed biomass based on LaFeO3 oxygen carrier prepared in Example 1 at 850°C and water vapor volume fraction of 20%;

[0033] Figure 7 Under the conditions of 850°C and 20% water vapor volume fraction, the LaFe prepared in Example 2 0.99 P 0.01 Gas component distribution results of chemical chain gasification of municipal sludge and cotton stalk mixed biomass with O3 oxygen carrier;

[0034] Figure 8 Under the conditions of 850°C and 20% water vapor volume fraction, the LaFe prepared in Example 3 0.97 P 0.03 Gas component distribution results of chemical chain gasification of municipal sludge and cotton stalk mixed biomass with O3 oxygen carrier;

[0035] Fig. 9 Under the conditions of 850°C and 20% water vapor volume fraction, the LaFe prepared in Example 4 0.95 P 0.05 Gas component distribution results of chemical chain gasification of municipal sludge and cotton stalk mixed biomass with O3 oxygen carrier;

[0036] Fig.10The results of direct gasification of a mixture of municipal sludge and cotton stalk biomass and the quartz sand of Comparative Example 1 under the conditions of 850°C and 20% water vapor volume fraction, and the gas yield and H2 / CO ratio of biomass chemical chain gasification based on the phosphorus-doped lanthanum iron perovskite oxygen carrier prepared in Examples 1 to 4;

[0037] Fig.11 XRD patterns of the oxygen carriers prepared in Examples 1 to 4 after one biomass chemical chain gasification redox cycle at 850°C and a water vapor volume fraction of 20%;

[0038] Fig.12 This is the XPS characterization result diagram of the oxygen carrier prepared in Examples 1 to 4. DETAILED DESCRIPTION

[0039] The present invention is further described below in conjunction with examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In the following examples, if the experimental method of the specific conditions is not indicated, it is usually carried out according to the conventional conditions in the art or according to the conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets. Any non-substantial changes and substitutions made by those skilled in the art on the basis of the present invention belong to the scope of protection claimed by the present invention.

[0040] A non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier according to an embodiment of the present invention has the general formula LaFe 1-x P x O3, 0≤x≤1.

[0041] The crystal structures of the above oxygen carriers are all cubic, indicating that doping with a small amount of phosphorus does not cause significant changes in the crystal structure of LaFeO3 perovskite, and the prepared phosphorus-doped lanthanum iron-based perovskite oxygen carrier has good structural stability.

[0042] Preferably, the value range of x is 0.01≤x≤0.05. According to the structural tolerance coefficient formula proposed by GoldSchmidt, the structural deviation t of the perovskite structure should be between 0.75 and 1. Therefore, with the increase of phosphorus doping, the perovskite will undergo obvious lattice contraction, and when x exceeds 0.05, it will be difficult for the P element to be doped into the perovskite B site, and the pure perovskite phase cannot be obtained.

[0043] The above oxygen carrier is a composite oxide oxygen carrier ABB'O3 with a perovskite structure, wherein the value of x ranges from 0≤x≤1, wherein A is a rare earth metal lanthanum, B is a transition metal iron, and B' is a non-metallic element phosphorus. The non-metallic phosphorus is used to partially replace the Fe in LaFeO3 perovskite without changing the crystal structure of the perovskite, thereby preparing a phosphorus-doped lanthanum iron-based perovskite oxygen carrier LaFe with a cubic crystal structure and different Fe:P molar ratios. 1-x P x O3.

[0044] The preparation method of the above-mentioned non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier comprises the following steps:

[0045] Step 10, according to LaFe 1-x P x O3 in a stoichiometric ratio, weigh 4.3300 parts by mass of La(NO3)3·6H2O, 4.0402(1-x) parts by mass of Fe(NO3)3·9H2O, 1.1503x parts by mass of NH4H2PO4, and a complexing agent, dissolve them in deionized water at a preset temperature, add ammonia water dropwise to the solution, adjust the pH value of the solution, and form a precursor solution.

[0046] Preferably, the complexing agent includes citric acid (CA) and ethylenediaminetetraacetic acid (EDTA), the molar ratio of citric acid to ethylenediaminetetraacetic acid is 2: 1, and the molar ratio of the complexing agent to the total amount of metal ions in the precursor solution is 3: 1. The preset temperature is 70-90° C., and the pH value of the precursor solution is 7-8.

[0047] In the process of preparing gel by evaporating the precursor solution, if the temperature is too low, metal nitrates are easy to precipitate, reducing the uniformity of the sample, and the sol is relatively viscous, affecting the stirring and dispersion effect; if the temperature is too high, it will lead to uneven evaporation, which will also affect the uniformity of the dry gel, so the temperature is selected to be 70-90°C. Citric acid is a polybasic weak acid, which will undergo multi-step dissociation in the solution. The dissociated ions exist in different equilibrium states at different pH values, causing different complexation modes between metal cations and citric acid, thereby affecting the polymerization effect. Therefore, the pH value of the precursor solution will affect the crystallization state and particle size of the product. When the pH value of the precursor solution is low, the degree of ionization of citric acid is low under strong acidic conditions, the number of coordinated hydroxyl groups is small, the metal cation complexation effect is poor, the gel contains a large amount of free metal cations, the precursor composition is uneven, and more impurities are finally formed; if the pH value of the precursor solution is too high, the metal cations in the solution will precipitate, affecting the purity of the product. Therefore, maintaining the precursor solution at a weakly alkaline condition of pH 7 to 8 is more suitable for preparing oxygen carriers with a pure perovskite phase.

[0048] Step 20, evaporate the precursor solution of step 10 to a gel state under stirring conditions, and then pre-combust to obtain a sponge-like porous precursor. Preferably, the stirring rate is 300-500 rpm, and the evaporation temperature is 100-120° C. Preferably, the pre-combustion is carried out in a muffle furnace at a pre-combustion temperature of 250° C.

[0049] Step 30, calcining the sponge-like porous precursor obtained in step 20 at a constant temperature to obtain the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier. Preferably, in step 30, the sponge-like porous precursor obtained in step 20 is transferred to a crucible and calcined at a constant temperature in a muffle furnace; the calcination temperature is 1000° C. and the calcination time is 5 hours.

[0050] The above oxygen carrier preparation method is simple, low-cost, and is conducive to industrial promotion and use. The method uses ammonium dihydrogen phosphate as a phosphorus source, which is low in cost and avoids the introduction of other metal elements during the preparation process. Compared with the traditional metal doping method using metal nitrate as the doping raw material, the method uses ammonium dihydrogen phosphate as a phosphorus dopant, and the surface of the prepared oxygen carrier has more active oxygen and oxygen vacancies, which is conducive to the production of synthesis gas by biomass chemical chain gasification.

[0051] The application of the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier in the biomass chemical chain gasification reaction, in the biomass gasification stage, the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier exchanges heat and mass with the biomass, and the lattice oxygen in the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier partially oxidizes the biomass to generate synthesis gas, and at the same time, the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier is reduced to generate a reduced oxygen carrier, the general formula of which is LaFe 1-x P x O 3-δ , the value range of δ is 0≤δ≤3; in the oxidation stage, the reduced oxygen carrier reacts with oxygen in the air to replenish oxygen and restores to the structure before reacting with biomass. The general formula is LaFe 1-x P x O3, thereby achieving the recycling regeneration of oxygen carriers.

[0052] Preferably, the raw material of the biomass is at least one of green algae, municipal sludge and cotton stalks, and the temperature of the gasification stage and the oxidation stage are both 750-950°C.

[0053] Preferably, in the biomass gasification stage, the gases introduced are nitrogen and water vapor, and the volume percentage of water vapor is 0-20%; nitrogen is the carrier gas and balance gas, and water vapor is used to adjust the H2 / CO ratio of the synthesis gas; in the oxidation stage, the gas introduced is air.

[0054] In the above application, in the biomass gasification stage, as shown in formula (1), the biomass (biomass) is first pyrolyzed to generate tar (tar), coke (biochar), small molecule gas (gas) and a small amount of ash (ash). As shown in formulas (2) and (3), thanks to the rich surface active oxygen species and oxygen vacancies of the phosphorus-doped lanthanum iron-based perovskite oxygen carrier, the biomass tar is catalytically oxidized into small molecule gas under the combined action of active oxygen and metal and non-metal active sites (Fe, P). As shown in formula (4), the coke reacts with the lattice of the oxygen carrier to generate CO, thereby promoting the generation of synthesis gas. In this process, as shown in formula (5), the oxygen carrier loses part of the lattice oxygen to generate the reduced oxygen carrier LaFe 1-x P x O 3-δ .

[0055] biomass → gas (H2, CO, CO2, CH4) + biochar + tar +ash Formula (1)

[0056] C n H m + Chemisorbed oxygen species → C i H j +CO+H2+CO2+H2O Formula (2)

[0057]

[0058] C+ lattice oxygen→CO Formula (4)

[0059] LaFe 1-x P x O3→LaFe 1-x P x O 3-δ +δO Formula (5)

[0060] In formula (2) and formula (3), C n H m It refers to the tar molecule.

[0061] In the oxidation stage, as shown in formula (6), the reduced oxygen carrier LaFe 1-x P x O 3-δ Reacts with oxygen in the air to replenish oxygen and restores the structure before reacting with biomass LaFe 1-x P x O3, thereby achieving the cyclic regeneration of oxygen carriers and releasing heat for the biogasification process.

[0062] LaFe 1-x P x O 3-δ+δ / 2O2→LaFe 1-x P x O3 formula (6)

[0063] The non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier of the above embodiment is applied to biomass chemical chain gasification, and has the advantages of good lattice oxygen fluidity and reaction activity, high synthesis gas yield and low tar content. 5+ Replaces the low-valent Fe in LaFeO3 3+ In order to maintain the electrical neutrality of the crystal structure, a low-valent Fe 2+ The formation of oxygen vacancies increases the mobility of lattice oxygen in the oxygen carrier and strengthens the conversion of lattice oxygen to surface adsorbed oxygen species, promoting the transformation of biomass tar into small molecule syngas, thereby reducing the tar content and increasing the syngas yield.

[0064] The present invention uses low-cost NH4H2PO4 as a doping raw material to dope LaFeO3 with non-metallic phosphorus at the B position. Using NH4H2PO4 as a doping raw material can significantly reduce the preparation cost. At the same time, the doping of phosphorus element can promote the generation of surface active oxygen species and oxygen vacancies, increase surface active sites, and facilitate the decomposition of macromolecular tar. The present invention uses NH4H2PO4 as a phosphorus source, which can effectively avoid the introduction of other metal ions, thereby avoiding the influence of alkali metals on the biomass chemical chain gasification.

[0065] Specific examples and comparative examples are provided below.

[0066] Comparative Example 1

[0067] Quartz sand is used as the bed material. The molecular formula of quartz sand is SiO2, CAS number: 14808-60-7.

[0068] 40 mg of quartz sand was measured and uniformly mixed with 100 mg of green algae (quartz sand to biomass mass ratio was 0.4:1) to form a mixture. 10 mg of the mixture was taken and placed in a synchronous thermal analyzer of model STA 409PC manufactured by NETZSCH, Germany, in an Ar atmosphere of 240 mL / min and a heating rate of 10°C / min from room temperature to 900°C for thermogravimetric analysis. Room temperature generally refers to 25°C.

[0069] Example 1 Preparation method of oxygen carrier LaFeO3

[0070] Step 10, weigh 4.3300g of lanthanum nitrate hexahydrate La(NO3)3·6H2O, 4.0402g of iron nitrate nonahydrate Fe(NO3)3·9H2O, 5.842g of ethylenediaminetetraacetic acid (EDTA) and 7.685g of anhydrous citric acid CA, dissolve them in deionized water at 85°C, and add ammonia water dropwise to the solution to adjust the pH value of the solution to 8 to form a precursor solution; wherein the molar ratio of EDTA:CA:metal ion is 1:2:1.

[0071] Step 20, evaporate the precursor solution of step 10 at 120°C to a gel state at a stirring rate of 300 rpm, then place it in a muffle furnace and heat it to 250°C at a heating rate of 5°C / min, keep it at this temperature for 5 hours, and pre-burn it to obtain a sponge-like porous precursor.

[0072] Step 30, transfer the sponge-like porous precursor obtained in step 20 into a crucible, heat it to 1000°C in a muffle furnace at a heating rate of 5°C / min, and keep it at a constant temperature for 5 hours, calcine to obtain undoped lanthanum iron-based perovskite oxygen carrier LaFeO3, and obtain 60-mesh oxygen carrier particles through screening.

[0073] Example 2 Oxygen carrier LaFe 0.99 P 0.01 Preparation method of O3

[0074] Step 10, weigh 4.3300 g of lanthanum nitrate hexahydrate La(NO3)3·6H2O, 3.9998 g of ferric nitrate nonahydrate Fe(NO3)3·9H2O, 0.0115 g of ammonium dihydrogen phosphate NH4H2PO4, 5.842 g of ethylenediaminetetraacetic acid (EDTA) and 7.685 g of anhydrous citric acid CA, dissolve them in deionized water at 70°C, and add ammonia water dropwise to the solution to adjust the pH value of the solution to 7, wherein the molar ratio of EDTA:CA:metal ion is 1:2:1.

[0075] Step 20, evaporate the precursor solution of step 10 at 110°C with a stirring rate of 400 rpm to a gel state, then place it in a muffle furnace and heat it to 250°C at a heating rate of 5°C / min, keep it at a constant temperature for 4 hours, and pre-burn it to obtain a sponge-like porous precursor.

[0076] Step 30, transferring the sponge-like porous precursor obtained in step 20 into a crucible, heating it to 1000°C in a muffle furnace at a heating rate of 5°C / min, and calcining it at a constant temperature for 5 hours to obtain a non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier LaFe 0.99 P 0.01 O3, after sieving, obtain 60 mesh oxygen carrier particles.

[0077] Example 3 Oxygen carrier LaFe0.97 P 0.03 Preparation method of O3

[0078] Step 10, weigh 4.3300 g of lanthanum nitrate hexahydrate La(NO3)3·6H2O, 3.919 g of ferric nitrate nonahydrate Fe(NO3)3·9H2O, 0.0345 g of ammonium dihydrogen phosphate NH4H2PO4, 5.842 g of ethylenediaminetetraacetic acid (EDTA) and 7.685 g of anhydrous citric acid CA, dissolve them in deionized water at 90°C, and add ammonia water dropwise to the solution to adjust the pH value of the solution to 7.5, wherein the molar ratio of EDTA:CA:metal ion is 1:2:1.

[0079] Step 20, evaporate the precursor solution of step 10 at 115°C with a stirring rate of 450 rpm to a gel state, then place it in a muffle furnace and heat it to 250°C at a heating rate of 5°C / min, keep it at a constant temperature for 4 hours, and pre-burn it to obtain a sponge-like porous precursor.

[0080] Step 30, transferring the sponge-like porous precursor obtained in step 20 into a crucible, heating it to 1000°C in a muffle furnace at a heating rate of 5°C / min, and calcining it at a constant temperature for 5 hours to obtain a non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier LaFe 0.97 P 0.03 O3, after sieving, 80-mesh oxygen carrier particles were obtained.

[0081] Example 4 Oxygen carrier LaFe 0.95 P 0.05 Preparation method of O3

[0082] Step 10, weigh 4.3300 g of lanthanum nitrate hexahydrate La(NO3)3·6H2O, 3.8382 g of ferric nitrate nonahydrate Fe(NO3)3·9H2O, 0.0575 g of ammonium dihydrogen phosphate NH4H2PO4, 5.842 g of ethylenediaminetetraacetic acid (EDTA) and 7.685 g of anhydrous citric acid CA, dissolve them in deionized water at 80°C, and add ammonia water dropwise to the solution to adjust the pH value of the solution to 7.8, wherein the molar ratio of EDTA:CA:metal ion is 1:2:1.

[0083] Step 20, evaporate the precursor solution of step 10 at 100°C to a gel state with a stirring rate of 500 rpm, then place it in a muffle furnace and heat it to 250°C at a heating rate of 5°C / min, keep it at this temperature for 4 hours, and pre-burn it to obtain a sponge-like porous precursor.

[0084] Step 30, transferring the sponge-like porous precursor obtained in step 20 into a crucible, heating it to 1000°C in a muffle furnace at a heating rate of 5°C / min, and calcining it at a constant temperature for 5 hours to obtain a non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier LaFe 0.95 P 0.05 O3, after sieving, 80-mesh oxygen carrier particles were obtained.

[0085] Experiments were conducted on the oxygen carriers prepared in Comparative Example 1 and Examples 1 to 4.

[0086] 1. X-ray diffraction (XRD) test was performed on the oxygen carriers prepared in Examples 1 to 4. Test conditions: The radiation source was Kα rays generated by Cu target, wavelength λ = 0.15418nm, the scanning rate was set to 10° / min, the scanning interval was set to 2θ = 10-90°, and the interval was 0.02°. The test instrument was a powder diffractometer of Rigaku Smartlab model of Japan Physical and Chemical Company. X-ray diffraction test was performed according to conventional methods. The test results are shown in Figure 1 As shown. Figure 1 (a) It can be seen that the prepared phosphorus-doped lanthanum iron-based perovskite oxygen carriers all have a perovskite phase with a single cubic crystal structure. Figure 1 (b) Yes Figure 1 (a) is an enlarged view of the dotted box. Figure 1 (b) The enlarged diffraction peak spectrum shows that as the phosphorus doping amount increases, the diffraction peak shifts to a larger diffraction angle. This is because the Fe 3+ P with smaller ionic radius 5+ This is caused by the replacement of the lattice, which also shows that phosphorus has been successfully doped into the bulk structure of LaFeO3 perovskite.

[0087] 2. The oxygen carrier LaFeO3 prepared in Example 1 and the oxygen carrier LaFe prepared in Example 3 0.97 P 0.03 O3 was tested by scanning electron microscopy (SEM) and energy spectrum (EDX-mapping). The test instruments were ZEISS sigma500 environmental scanning electron microscope (FE-SEM) and JEM-2100F X-ray fluorescence spectrometer. Scanning electron microscopy and energy spectrum tests were performed according to conventional methods. The test results are shown in Figure 2. It can be seen from Figure 2(a) and Figure 2(b) that LaFeO3 and phosphorus-doped LaFe 0.97 P 0.03 The O3 perovskite oxygen carrier is in the form of fine particles with uniform grain size and good dispersion. As can be seen from Figure 2(c) and Figure 2(d), the LaFeO3 oxygen carrier prepared by the method of the present invention contains La, Fe and O elements, while LaFe 0.97 P 0.03The O3 oxygen carrier contains not only La, Fe and O elements, but also phosphorus element, which indicates that the preparation method of the present invention successfully doped phosphorus element into the bulk structure of LaFeO3 perovskite.

[0088] 3. Synchronous thermal analysis experiment: The synchronous thermal analyzer used is a synchronous thermal analyzer of model STA409PC manufactured by German manufacturer NETZSCH.

[0089] The experimental method is as follows: 40 mg of oxygen carrier is measured and mixed evenly with 100 mg of green algae to form a mixture. The mass ratio of oxygen carrier to biomass is 0.4:1. 10 mg of the mixture is placed in a synchronous thermal analyzer, and the temperature is raised from room temperature to 900°C at a set heating rate in an Ar atmosphere of 240 mL / min for thermogravimetric analysis.

[0090] The oxygen carriers prepared in Comparative Example 1 and Examples 1 to 4 were respectively subjected to experiments, and the heating rate was set to 40° C. / min.

[0091] The experimental results are as follows Figure 3 . Figure 3 In the figure, the horizontal axis represents the reaction temperature in °C; the vertical axis represents the weight loss of the sample in wt.%. Figure 3 It can be seen that compared with the addition of comparative example 1, the weight loss of green algae after adding oxygen carriers of Examples 1 to 4 increased significantly, and the weight loss of the oxygen carriers after phosphorus doping was greater than that of LaFeO3 not doped with phosphorus. According to the heating rate of 40°C / min, the weight loss after phosphorus doping was greater. This shows that the conversion rate of green algae is higher under the condition of the same amount of oxygen carrier added, proving that phosphorus doped oxygen carriers are more beneficial to the conversion of green algae biomass.

[0092] 4. Mass spectrometry analysis experiment: The mass spectrometer used was Thermo Fisher Scientific iS 50.

[0093] The experimental method is: measure 40 mg of oxygen carrier and mix it evenly with 100 mg of green algae to form a mixture. The mass ratio of oxygen carrier to biomass is 0.4:1. Take 10 mg of the mixture in a synchronous thermal analyzer, in an Ar atmosphere of 240 mL / min, and heat it from room temperature to 900°C at a heating rate of 40°C / min. The generated gas enters the mass spectrometer, and the gas components are detected online by the mass spectrometer. The generated gas components, for comparative example 1, include CO, CO2, H2, CH4; for examples 1-4, include CO and H2.

[0094] In the experiment, the above mass spectrometry analysis experiment was performed on the oxygen carriers prepared in Comparative Example 1 and Examples 1-4. Figure 4 shown. Figure 4In the figure, the horizontal axis represents the reaction temperature, unit: °C; the vertical axis represents the ion current intensity of each sample gas component; MA represents the sample of Comparative Example 1, MA-LF represents the sample of Example 1, MA-LFP1 represents the sample of Example 2, MA-LFP3 represents the sample of Example 3, and MA-LFP5 represents the sample of Example 4. Figure 4 It can be seen that compared with the direct pyrolysis of green algae biomass and quartz sand and the mixed samples of green algae biomass and undoped LaFeO3 oxygen carrier, phosphorus-doped LaFe 1-x P x O3 (0.01≤x≤0.05) oxygen carrier can significantly promote the generation of syngas. After 750℃, the amount of CO generated increases significantly. This indicates that the lattice oxygen in the phosphorus-doped perovskite oxygen carrier enhances the gasification of biomass char to produce CO.

[0095] 5. Biomass chemical chain gasification reaction experiment: The gas analyzer used is the MRU VARIO PLUS gas analyzer.

[0096] 0.2g of municipal sludge with a particle size of 0.1-0.125μm and 0.3g of cotton stalk biomass particles with a particle size of 0.1-0.125μm were measured and mixed evenly to make a biomass mixture. The mass ratio of municipal sludge to cotton stalk was 2:3. 0.2g of oxygen carrier was weighed and mixed evenly with the biomass mixture, and then placed in a crucible for standby use. The mass ratio of oxygen carrier to biomass mixture was 0.4:1. Under a 200mL / min N2 atmosphere, the fixed bed reactor was heated from room temperature to 850℃ at a heating rate of 10℃ / min. When the temperature stabilized, water vapor with a volume fraction of 20% was introduced, and then the crucible containing the oxygen carrier and biomass mixture was placed in the reaction area of ​​the reactor, and the gas components were analyzed using a gas analyzer. After the reaction was completed, air was introduced to oxidize the oxygen carrier. The oxygen carrier used is in an oxidized state because it is calcined in an air atmosphere during the preparation process. It is reduced after reacting with the biomass. After the biomass gasification reaction, oxygen is introduced to achieve re-oxidation of the oxygen carrier. This process is a cycle.

[0097] The above experiment was carried out on the oxygen carriers of Comparative Example 1 and Examples 1 to 4 respectively. Figures 5 to 10 shown. Figures 5 to 9 The graph shows the change of gas components with reaction time under different oxygen carrier conditions, where the abscissa represents the reaction time and the ordinate represents the gas volume fraction. Fig.10 is the cumulative yield of each gas component in the above process, where the horizontal axis is the type of oxygen carrier and the vertical axis is the gas yield, unit: m 3 / kg. Fig.10It can be seen that compared with quartz sand and undoped LaFeO3 oxygen carriers, the yield of syngas in the biomass chemical chaining gasification process using phosphorus-doped perovskite oxygen carriers is significantly improved. This shows that phosphorus-doped perovskite oxygen carriers have good reactivity and can promote the directional conversion of tar macromolecules to small molecule syngas.

[0098] like Fig.11 As shown in FIG. 1 , the XRD spectrum of the phosphorus-doped perovskite oxygen carrier after a biomass chemical chain gasification cycle reaction. Fig.11 It can be seen that compared with the perovskite oxygen carrier that has been prepared but has not yet participated in the biomass chemical chain gasification cycle reaction, the oxygen carrier that has undergone a cycle reaction still has an obvious cubic perovskite structure. This shows that the reduced phosphorus-doped perovskite oxygen carrier LaFe 1-x P x O 3-δ After oxidation, it can be restored to its original structure LaFe 1-x P x O3.

[0099] 6. X-ray photoelectron spectroscopy (XPS) analysis experiment. The Thermo EscaLab 250Xi XPS spectrometer was used, with an Al Kα X-ray source (hν=1486.6eV) and a resolution of 0.25eV. The electron binding energy value was calibrated using the sample contamination carbon (C1s=284.8eV) as the internal standard. XPSPEAK 41 software was used, using a Shirley or Liner background, and applying a Voigt function with an indefinite Lorentz component for component deconvolution, and performing peak fitting processing on the XPS spectrum. XPS analysis was performed on the oxygen carriers prepared in Examples 1 to 4. The analysis results are shown in the figure. Fig.12 shown. Fig.12 In, O I Represents physically adsorbed oxygen species, generally existing in the form of adsorbed water molecules; O II represents the surface chemically adsorbed oxygen species; O III represents electron-rich superoxide, whose concentration is closely related to the content of surface oxygen vacancies; O IV is the lattice oxygen species. II and O III The content of is closely related to the activity of the oxygen carrier. Fig.12 It can be seen that after phosphorus doping, the surface O II +O III This indicates that phosphorus doping can significantly increase the oxygen activity of the oxygen carrier. 2+ The ratio increases with the increase of phosphorus doping amount, indicating that phosphorus is successfully embedded into the perovskite bulk phase.

[0100] The above is only a preferred embodiment of the present invention. It should be noted that those skilled in the art will realize that the above specific embodiments are only illustrative and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made by those skilled in the art under the guidance of the present invention shall be included in the protection scope of the present invention.

Claims

1. A non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier, characterized in that: The general formula of the oxygen carrier is LaFe 1- x P x O3, the value range of x is 0<x≤1; The oxygen carrier is prepared by the following steps: Step 10, according to LaFe 1-x P x O3 stoichiometric ratio, weigh 4.3300 parts by mass of La(NO3)3·6H2O, 4.0402(1-x) parts by mass of Fe(NO3)3·9H2O, 1.1503x parts by mass of NH4H2PO4, and a complexing agent, dissolve them in deionized water at a preset temperature of 70-90°C, and add ammonia water dropwise to the solution to adjust the pH value of the solution to form a precursor solution; the pH value of the precursor solution is 7-8; Step 20, evaporating the precursor solution of step 10 to a gel state under stirring conditions, and then pre-combusting to obtain a sponge-like porous precursor; Step 30, calcining the sponge-like porous precursor obtained in step 20 at a constant temperature to obtain the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier.

2. The non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier according to claim 1, characterized in that: The crystal structure of the oxygen carriers is cubic.

3. The non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier according to claim 1, characterized in that: The value range of x is 0.01≤x≤0.

05.

4. A method for preparing the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier as claimed in claim 1, characterized in that: The method comprises the following steps: Step 10, according to LaFe 1-x P x O3 stoichiometric ratio, weigh 4.3300 parts by mass of La(NO3)3·6H2O, 4.0402(1-x) parts by mass of Fe(NO3)3·9H2O, 1.1503x parts by mass of NH4H2PO4, and a complexing agent, dissolve them in deionized water at a preset temperature of 70-90°C, and add ammonia water dropwise to the solution to adjust the pH value of the solution to form a precursor solution; the pH value of the precursor solution is 7-8; Step 20, evaporating the precursor solution of step 10 to a gel state under stirring conditions, and then pre-combusting to obtain a sponge-like porous precursor; Step 30, calcining the sponge-like porous precursor obtained in step 20 at a constant temperature to obtain the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier.

5. The preparation method according to claim 4, characterized in that: In the step 10, the complexing agent includes citric acid and ethylenediaminetetraacetic acid, the molar ratio of citric acid to ethylenediaminetetraacetic acid is 2:1, and the molar ratio of the complexing agent to the total amount of metal ions in the precursor solution is 3:

1.

6. The preparation method according to claim 4, characterized in that: In the step 20, the stirring rate is 300-500 rpm, the evaporation temperature is 100-120° C., and the pre-combustion is carried out in a muffle furnace at a pre-combustion temperature of 250° C.; In the step 30, the sponge-like porous precursor obtained in the step 20 is transferred into a crucible and calcined at a constant temperature in a muffle furnace. The calcination temperature is 1000° C. and the calcination time is 5 hours.

7. An application of the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier as claimed in any one of claims 1 to 3 in a biomass chemical chain gasification reaction, characterized in that: In the biomass gasification stage, the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier exchanges heat and mass with the biomass, and the lattice oxygen in the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier partially oxidizes the biomass to generate synthesis gas, while the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier is reduced to generate a reduced oxygen carrier; In the oxidation stage, the reduced oxygen carrier reacts with oxygen in the air to replenish oxygen and restores the structure before reacting with the biomass, thereby achieving the cyclic regeneration of the oxygen carrier.

8. The use of the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier in biomass chemical chain gasification reaction according to claim 7, characterized in that: The raw material of the biomass is at least one of green algae, municipal sludge and cotton stalks, and the temperature of the gasification stage and the oxidation stage are both 750-950°C.

9. The use of the non-metallic phosphorus-doped lanthanum iron-based perovskite oxygen carrier in biomass chemical chain gasification reaction according to claim 7, characterized in that: In the biomass gasification stage, the gases introduced are nitrogen and water vapor, and the volume percentage of water vapor is 0-20%; in the oxidation stage, the gas introduced is air.

Citation Information

Patent Citations

  • Phosphor-doped dual-function perovskite-based catalyst and preparation method thereof

    CN107486212A

  • Preparation method of biochar loaded with lanthanum-doped iron oxide

    CN110813239A